Association Study of the Complement Component C4 Gene in Tardive Dyskinesia - Zai, Clement C.; Tiwari, Arun K.; Zai, Gwyneth C.; Freeman, Natalie; Pouget, Jennie G.; Greco, James; Tampakeras, Maria; Shaikh, Sajid A.; Herbert, Deanna; Emmerson, Heather; Cheema, Sheraz Y.; Braganza, Nicole; et al. (Frontiers in Pharmacology, 2019)
Tardive Dyskinesia (TD) is a movement disorder that may develop in schizophrenia patients being treated long-term with antipsychotic medication. TD interferes with voluntary movements and leads to stigma, and can be associated with treatment non-adherence. The etiology of TD is unclear, but it appears to have a genetic component. There is emerging evidence of immune dysregulation in TD. In the current study, we set out to investigate the complex schizophrenia-associated complement component 4 (C4) gene for possible association with TD occurrence and TD severity as assessed by the Abnormal Involuntary Movement Scale (AIMS) in a sample of 129 schizophrenia patients of European ancestry. We have genotyped the copy numbers of long and short forms of C4A and C4B gene variants in 129 European ancestry patients with schizophrenia or schizoaffective disorder. We did not find predicted C4A or C4B expression to be associated with TD risk or severity. However, we found the number of copies of C4BL to be associated with TD severity (p=0.038).